Proliferation, migration, and osteogenic differentiation of mesenchymal stem cells exposed to a nanocomposite of hydroxyapatite and doped gelan gum (Research, Society and Development, 2025)
Early tissue loss requires research aimed at developing innovative approaches for treatment and accelerating the regenerative process. Bone tissue injuries cause significant social and economic impacts and are the focus of studies seeking to improve regeneration. Bone marrow-derived mesenchymal stem cells (BMSCs) are promising candidates for this type of application. In this study, a novel biomaterial composed of hydroxyapatite and gellan gum doped with cerium ions was used. This composite exhibits structural similarities to gum arabic, previously employed in other studies, and provides relevant and significant advantages for application in osteogenesis. The aim of this work was to evaluate the cytotoxicity of the biomaterial and its effects on the proliferation, adhesion, migration, and osteogenic differentiation of bone marrow-derived mesenchymal stem cells. Complete bone regeneration depends on the presence of osteoinductive agents such as cells or biomolecules. Several biomaterials have been developed and applied in animal models to accelerate this process, including calcium phosphate cements and biopolymers. One of the major advances in this field is the use of biomaterials as scaffolds for cell integration, maintenance, and differentiation. The cells that constitute tissues and organs are embedded in a complex molecular network known as the extracellular matrix (ECM), whose molecules promote signaling pathways that direct cell growth and differentiation.